Breast reconstructions: an evolutionary analysis of techniques and current state of the art - José Carlos Daher; Carolina Oliveira Paranagua; Tristão Maurício de Aquino; Phabio Claudino Estrela Terra Theodoro; Ognev Meireles Cosac; Suellen Vieira da-Silva (Revista Brasileira de Cirurgia Plástica, 2022)
Introduction: The cancer that most affects women around the world is breast cancer. If the harm that the active disease is capable of causing was not enough, after the cure, the consequences continue to torment the lives of thousands of women. Furthermore, the psychological trauma of mutilation can have psychological repercussions that are difficult to control. Mastectomy saves the life of a woman with breast cancer; however, breast loss can keep the patient sick in the biopsychosocial aspect. Rebuilding the breasts then becomes crucial in the treatment of these women. Methods: The study of the authors’ public and personal collections allowed us to discuss the artistic and technical evolution of breast reconstructions over the years. Results: Studies and reflections from plastic surgeons worldwide have enabled the standardization of a series of techniques and tools for breast reconstruction that will make up the arsenal of the modern surgeon. It includes techniques with local flaps, such as the plug flap and mammoplasty techniques, neighborhood flaps, such as the thoracodorsal flap, alloplastic materials (tissue expanders and prostheses), the numerous autologous flaps, including microsurgical flaps or, also, the combined techniques for the various types of cases. At the same time, the medical-hospital products industry has developed alloplastic materials (prostheses and expanders) that are more suitable and of better quality, which provide safer and more predictable reconstructions concerning the use of implants. Conclusion: The current state of the art in breast reconstruction finds well-founded historical pillars and advanced technological aid, providing conditions for advanced treatments.